Design, synthesis, and biological evaluation of some novel 4-aminoquinazolines as Pan-PI3K inhibitors. Issue 13 (1st July 2019) - Ding, Huai-Wei; Wang, Shu; Qin, Xiao-Chun; Wang, Jian; Song, Hong-Rui; Zhao, Qing-Chun; Song, Shao-Jiang
Graphical abstract: Highlights: A series of 4-aminoquinazolines derivatives containing 6-sulfonamide substituted pyridyl group were designed. 4-Aminoquinazolines derivatives acted as potent Pan-PI3K inhibitors. Compound7b could be as potential PI3Kα inhibitor with an IC50 value of 0.20 nM. Compound 7b could decrease the phospho-Akt (T308) in a dose-dependent manner. Abstract: A series of 4-aminoquinazolines derivatives containing hydrophilic group were designed and identified as potent Pan-PI3K inhibitors in this study. The results of antiproliferative assays in vitro showed that this series of compounds had strong inhibition of tumor growth, especially compound7b for MCF-7 cells but weak inhibition to normal cells. PI3K kinase assay showed that7b had high activity for three PI3K isoforms with the IC50 values of picomole. The western blot assay indicated that7b could decrease the phospho-Akt (S473) in a dose-dependent manner. Further experiments showed that7b could induce apoptosis in MCF-7 cells. Four key hydrogen bonding interactions were found in the docking of7b with PI3K kinase. All these results suggested that7b is a potent PI3K inhibitor and could be considered as a potential candidate for the development of anticancer agents.